(3GdeSGFd hGdCLhHI aj afhf TJis - (3GdHWdjhSjs
(3ChdgG (B:s
(3jHOC HeSCdI ai GSe Gddg JYGdi hgj eHfjI Ydi CHhGH hajgG ONhd Gdeje Ydjg hbhdge Gddge EdN s
(3BNQgG (B:s
(3jfJgi HeSFdI ai bhd GdTGYQ (B: (3YjhG HCeQge ceG YjjJ HHjVJgG GdMeGeI LYdJ dgG YhOjf ef fTe hBNQ ef KeGeI s
(3HgG fXGe GdJYbjHIs
(3jMJhiYdi (B77 (3eSCdI ai afhf TJi hGdZGdH YdjgG GdfMh hGdUQa hbO SbWJ efgG GdeSCdI (B22s
(3hCSbW GdfGSN GdeSCdI (B74 (3dCfg hLOgG Yjf GdeSCdI (B40 s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs